Preserving The Cultural Practice of Processions by Packaging Healthy, Nutritious Food to Enhance Pride in Ancestral Culture - Nurul Hidayah; Septia Purwandari; Arshy Prodyanatasari; Rizky Aulia Fitriana; Indira Mustika Tandiono; Mifta Wahyu Rafa Sakina; Ana Nur Filia (Jurnal Gizi Prima (Prime Nutrition Journal), 2025)
Background: . The Buceng Guyup procession has become an annual event during the village cleansing ceremony, where seventeen buceng are collected from all neighborhood units (RW) in Sanan Wetan Village, showcasing local agricultural products from the area. This procession symbolizes the villagers' gratitude for their numerous blessings.Research Methods: This research employs qualitative methods, enabling the researcher to directly observe phenomena and provide genuine and relevant insights based on interviews with knowledgeable individuals, such as village elders, community leaders, and religious figures. The Spradley concept is utilized to identify informants and gather first-hand data from the researcher in the field.Research Result: The noble values contained in Buceng Guyup, such as gratitude, sharing, and togetherness, contribute to the enhancement of happiness and psychological well-being for both individuals and the community. Buceng Guyup often involves preparing nutritious food together, indirectly raising community awareness about the importance of nutritious food for physical and mental health. Nutritious food plays a crucial role in maintaining mental and emotional health, as good nutritional intake can prevent mental health issues such as depression and anxiety and improve cognitive function.Conclusion: This is undoubtedly related to beliefs, attitudes, and social norms. Promoting nutritious food must consider these factors so that the messages conveyed are effective and can change community eating behaviors toward healthier choices. A sense of pride in ancestral culture is an important part of an individual's cultural identity; it strengthens the sense of belonging, self-identity, and self-esteem of individuals as part of that cultural group. Pride in ancestral culture helps individuals discover and reinforce their identities. We can build a healthier, happier, and stronger community by understanding and leveraging the connections between Buceng Guyup, nutritious food, and pride in ancestral culture.